Autoimmune Vestibulocerebellar Syndromes - Narayan, Ram N.; McKeon, Andrew; Fife, Terry D. (Seminars in Neurology, 2020)
Autoimmune disorders affecting the vestibular end organs, vestibular pathways, vestibular nuclei, and vestibulocerebellum are often underrecognized as a cause of chronic dizziness and ataxia. Autoantibodies specific for cell-surface, synaptic, and intracellular neural antigens serve as biomarkers of these disorders. This article describes the epidemiology, clinical presentation, diagnostic considerations, imaging findings, treatment, and prognosis of autoimmune disorders, in which the vestibulocerebellar syndrome is the main or presenting clinical presentation. Antibodies specific for intracellular antigenic targets described in the article are PCA-1 (Purkinje cell cytoplasmic antibody type 1, also known as anti-Yo), ANNA-1 (antinuclear neuronal antibody type 1, also known as anti-Hu), ANNA-2 (antinuclear neuronal antibody type 2, also known as anti-Ri), Ma1/2 (anti-Kelch-like 11/12 antibody), Kelch-like 11, amphiphysin, CV2 (collapsin response 2, also known as collapsin response mediator protein-5 [CRMP5]), VGCC (voltage-gated calcium channel), GAD65 (glutamic acid decarboxylase 65-kDa isoform), AP3B2 (adaptor protein 3B2, also known as anti-Nb), MAP1B (microtubule-associated protein 1B antibody, also known as anti-PCA-2), and neurochondrin antibodies. Antibodies targeting cell-surface or synaptic antigenic targets described in the article include DNER (delta/notchlike epidermal growth factor related receptor; antigen to anti-Tr), CASPR2 (contactin-associated proteinlike 2), septin-5, Homer-3, and mGluR1 (metabotropic glutamate receptor 1). The vestibulocerebellar presentation is largely indistinguishable among these conditions and is characterized by subacute onset of cerebellar symptoms over weeks to months. The diagnosis of autoimmune vestibulocerebellar syndromes is based on a combination of clinical and serological features, with a limited role for neuroimaging. Subtle eye movement abnormalities can be an early feature in many of these disorders, and therefore a meticulous vestibulo-ocular examination is essential for early and correct identification. Cancer occurrence and its type are variable and depend on the autoantibody detected and other cancer risk factors. Treatment comprises immunotherapy and cancer-directed therapy. Acute immunotherapies such as intravenous immunoglobulin, plasma exchange, and steroids are used in the initial phase, and the use of long-term immunosuppression such as rituximab may be necessary in relapsing cases. Outcomes are better if immunotherapy is started early. The neurologic prognosis depends on multiple factors.
Keywords: autoimmune cerebellar ataxia; central nervous system; vestibulocerebellar syndromes; autoimmune encephalitis; downbeat nystagmus